Physics Learning Strategy on Sound for Autism Phase F Students in Special Needs School - Tahir, Hasan; Umar, Masri Kudrat; Mohamad, Wahyu Muzizat (Kasuari: Physics Education Journal (KPEJ), 2025)
This research aims to describe the learning strategies applied by teachers in teaching the physics concept of sound to Phase F autistic students in a Special Needs School. The study uses a qualitative descriptive method, focusing on one autistic student in Phase F and four intellectually disabled students as supporting subjects. Data were collected through observation, interviews with the teacher, and documentation of learning activities. The results show that the teacher implemented visual and multisensory-based strategies using an individual approach and two-way communication through facial expressions, body movements, and visual media. Teaching aids such as pictures of musical instruments, short videos, and whiteboard writings significantly helped students understand the sound concept. Although the strategies increased students' engagement and attention, challenges arose during lesson closures, where reflective and summarizing activities were lacking. Teachers also faced difficulties ensuring student comprehension of verbal instructions, which were addressed through written instructions and visual demonstrations. The study recommends developing concrete experience-based strategies, repeated reinforcement, and structured learning environments tailored to the characteristics of Phase F autistic students.